Electronic Word of Mouth (e-WOM) Foursquare: The New Social Media - Rita, Rita; Hutomo, Karyana; Natalia, Natalia (Bina Nusantara University, 2013)
The development of communication technology and Internet-based information encourage the emergence of new changes in the marketing world. Customer-oriented makes it an effective medium for the activities of Word-of-Mouth (WOM). In this information era, Word-of-Mouth becomes credible resource in the community. To harness the power of electronic Word-of-Mouth (e-WOM), the company must first identify and understand effectively users of the web to spread their opinions. By using 60 respondents as a source of information and data collection, results of the study found various types of Foursquare users and various motivations that drive them. The first finding of this study revealed six types of Foursquare users, namely: The Gamers, The Existence, The Need Help, The Mayor, The Showoff, and the Angels. The second finding was the type of motivation that Foursquare users are distinguished by category Feature Involvement, Self Satisfaction, Seeking Advice, Economic Incentives, Self Enhancement, and Concern for Other Users. From this study, Self Satisfaction, Self Enhancement, and Concern for Other Users are the motivation type of Foursquare users that give positive contribution to the activities of e-WOM because the three types directly doÂ some sort recommendations or promotions of the places they check-in. Furthermore, Feature Involvement, Seeking Advice, and Economic Incentives are the types that less provide positive contribution to the activities of e-WOM. Advice Seeking and Economic Incentives are the types that the most feel benefits of e-WOM activities through Foursquare. Feature Involvement is the type that does not contribute the most to the activities of e-WOM and do not feel the most benefits of e-WOM activities through Foursquare. This research is expected to help companies that use Foursquare to establish the right business strategy in encouraging e-WOM among Foursquare users.